2022
DOI: 10.3390/cancers14071839
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Genetic Testing for All Women Diagnosed with Breast Cancer in China

Abstract: Unselected multigene testing for all women with breast cancer (BC) identifies more cancer susceptibility gene (CSG) carriers who can benefit from precision prevention compared with family history (FH)/clinical-criteria-based guidelines. Very little CSG testing is undertaken in middle-income countries such as China, and its cost-effectiveness remains unaddressed. We aimed to estimate cost-effectiveness and population impact of multigene testing for all Chinese BC patients. Data from 8085 unselected BC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…Three studies [ 23 , 26 , 27 ] targeted urban settings and one study [ 24 ] focused on rural areas. Only one of five identified articles analyzed the cost-effectiveness of unselected multigene testing strategies ( BRCA1 / BRCA2 / PALB2 testing, family history/clinical criteria-based BRCA testing) for all Chinese patients with breast cancer [ 25 ]. The main comparator in all studies was non-screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies [ 23 , 26 , 27 ] targeted urban settings and one study [ 24 ] focused on rural areas. Only one of five identified articles analyzed the cost-effectiveness of unselected multigene testing strategies ( BRCA1 / BRCA2 / PALB2 testing, family history/clinical criteria-based BRCA testing) for all Chinese patients with breast cancer [ 25 ]. The main comparator in all studies was non-screening.…”
Section: Resultsmentioning
confidence: 99%
“…The main comparator in all studies was non-screening. Four studies incorporated additional comparators of varied screening intervals or different target populations [ 23 , 25 27 ]. The sample size varied between 26,244 and 1,252,074, wherein two studies used 100,000 hypothetical cohorts in their model [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Around 36.8% of colorectal cancer studies reported testing costs over US$ 2000, a stark contrast to 18.2% studies with similar pricing in HBOC. A few recent studies 17,20,21,25,45,46 saw a reduction in price of testing, yet for the most part costs remained highly variable across settings. 27,47 Assumptions on uptake of prophylactic risk reduction surgeries also influenced results and was the most predominant factor affecting cost-effectiveness in HBOC studies.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several additional studies on the cost-effectiveness of germline testing since the previous reviews. [16][17][18][19][20][21][22][23][24][25][26] Some of them assessed population-wide testing, 17,20 while others, evaluated the cost-utility of A c c e p t e d M a n u s c r i p t germline testing guided treatments in cancer patients with mutations. 26 Next-generation sequencing (NGS) has also become affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Another notable issue concerns the price of BRCA mutation testing ( 84 ). Currently the price of BRCA mutation testing for a single sample in China is roughly 300 dollars ($), which is only paid by the patient side and not covered by the government side through basic medical insurance ( 85 ). Actually, the price of a single BRCA mutation testing is too high for the majority of ordinary Chinese.…”
Section: Problems Related To Panel Sequencingmentioning
confidence: 99%